Children on the Move : Progressive Redistribution of Humanitarian Cash Transfers among Refugees - Ozler, Berk; Celik, Cigdem; Cunningham, Scott; Cuevas, P. Facundo; Parisotto, Luca (World Bank, Washington, DCW, 2020)
This paper evaluates the impact of the Emergency Social Safety Net (ESSN) in Turkey, the largest cash transfer program for international refugees in the world. The paper provides prima facie evidence that the program quickly caused substantial changes in household size and composition, with a net movement of primarily school-age children from larger ineligible households to smaller eligible ones. A sharp decline in inequality is observed in the entire study population: the Gini index declined by four percentage points (or 15 percent) within six months of program rollout, and the poverty headcount at the $3.20/day international poverty line declined by more than 50 percent after one year. ESSN caused a moderate increase in the diversity and frequency of food consumption among eligible households, and although there was no statistically significant effect on overall school enrollment, there were meaningful gains among the most vulnerable beneficiary households. To strike the right balance between transfer size and coverage, key parameters in the design of any cash transfer program, policy makers should consider the possibility that refugee populations may respond to their eligibility status by altering their household structure and living arrangements.